Influencia de diferentes periodos de interferencia de malezas en el crecimiento y rendimiento del cultivo de cúrcuma (Curcuma amada Roxb.) - Oke, H. (2024)
Field trials were conducted in the early and late wet cropping seasons of  2017 at Institute of Agricultural Research and Training, Ikenne Station to evaluate the critical period of weed interference in mango ginger. Twelve weed inference periods were evaluated and laid out in a randomized complete block design with three replications. Data were collected on growth parameters, yield, weed cover score and weed dry matter production. Results showed that keeping mango ginger free of weed for at least 8 WAP (weeks after planting) resulted in better crop growth than when left weed infested for 8 WAP and beyond. Mango ginger yield increased significantly with increase in weed free period from 4 weeks to 12 weeks, beyond which there was no significant yield increase. In early and late cropping seasons respectively, there was 18.7 % and 15.6 % yield loss when mango ginger was left weed infested for the first 4 weeks, while there was further 36.1 % and 39.1 % yield loss with additional weed infestation for another 4 weeks till 8 WAP. Therefore, first 8 weeks of production of mango ginger is crucial and should be kept weed free as this period is critical in the production of the crop.